2007
DOI: 10.1002/cncr.23001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a multiple epigenetic marker panel for lung cancer detection and risk assessment in plasma

Abstract: BACKGROUND.Methylation patterns may be useful biomarkers of cancer detection and risk assessment.METHODS.The methylation status of 6 genes, including a candidate tumor suppressor gene (BLU), the cadherin 13 gene (CDH13), the fragile histidine triad gene (FHIT), the cell cycle control gene p16, the retinoic acid receptor β gene (RARβ), and the Ras association domain family 1 gene (RASSF1A), was examined in plasma samples, corresponding tumor tissues, and normal lung tissues from a group of 63 patients with lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
83
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(87 citation statements)
references
References 53 publications
0
83
2
1
Order By: Relevance
“…It has been suggested that RASSF1A methylation is one of the most common aberrations so far identified in human cancers and that the loss of the functional protein may promote the development of many human tumors. Hypermethylation of the RASSF1A has been detected frequently in the tissues of different cancers [10][11][12][13][14][15][16][17], while in the body fluid, methylation of RASSF1A promoter has also been documented in 50% sputum and 84% serum from lung cancer [30], 35% urine from bladder cancer [15], 56-60% serum from breast caner [31][32][33], and 5% serum from undifferentiated nasopharyngeal carcinoma [34], which indicated the value of RASSF1A methylation in DNA for the early-stage diagnosis of tumors. Detection of methylated DNA has then been suggested as a potential biomarker for early detection of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that RASSF1A methylation is one of the most common aberrations so far identified in human cancers and that the loss of the functional protein may promote the development of many human tumors. Hypermethylation of the RASSF1A has been detected frequently in the tissues of different cancers [10][11][12][13][14][15][16][17], while in the body fluid, methylation of RASSF1A promoter has also been documented in 50% sputum and 84% serum from lung cancer [30], 35% urine from bladder cancer [15], 56-60% serum from breast caner [31][32][33], and 5% serum from undifferentiated nasopharyngeal carcinoma [34], which indicated the value of RASSF1A methylation in DNA for the early-stage diagnosis of tumors. Detection of methylated DNA has then been suggested as a potential biomarker for early detection of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the prevalence of RASSF1A methylation is exhibited in 30-40% of NSCLC, and is mainly detected by methylation-specific PCR (MSP) analysis Toyooka et al, 2003;Guo et al, 2004;Wang et al, 2004;Choi et al, 2005;Dammann et al, 2005;Ito et al, 2005;Chen et al, 2006;Hsu et al, 2007;Yanagawa et al, 2007;Yang et al, 2007;Liu et al, 2008;Lin et al, 2009;Peng et al, 2010;Zhang et al, 2010;Kang et al, 2011;Song et al, 2011;. However, association of RASSF1A promoter methylation with NSCLC have mostly been investigated in studies with small sample sizes or other limitations in study design, leading to conflicting results, especially in the relationship between RASSF1A promoter methylation and clinicopathologic features among NSCLC.…”
Section: Associations Between Rassf1a Promoter Methylation and Nsclc:mentioning
confidence: 99%
“…Moreover, one was excluded as a duplicate publication . Ultimately, 19 publications met the inclusion criteria (Figure 1) Toyooka et al, 2003;Guo et al, 2004;Wang et al, 2004;Choi et al, 2005;Dammann et al, 2005;Ito et al, 2005;Chen et al, 2006;Hsu et al, 2007;Kim et al, 2007;Yanagawa et al, 2007;Yang et al, 2007;Liu et al, 2008;Lin et al, 2009;Peng et al, 2010;Zhang et al, 2010;Kang et al, 2011;Song et al, 2011;Li et al, 2012) and were included in the meta-analysis. Detailed characteristics of the 19 studies are listed in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations